Association of serum organochlorine pesticides concentrations with reproductive hormone levels and polycystic ovary syndrome in a Chinese population. (March 2017) - Guo, Zhizhun; Qiu, Huiling; Wang, Lingling; Wang, Lijun; Wang, Chonggang; Chen, Meng; Zuo, Zhenghong
Abstract: To investigate the serum concentrations of organochlorine pesticides (OCPs) in patients with polycystic ovary syndrome (PCOS), a total of 178 women were studied. The concentrations of hexachlorocyclohexane (HCH) and dichlorodiphenyltrichloroethane (DDT) in serum were determined using Gas Chromatography Mass-Mass Spectrometer. No differences with statistical significance in the mean HCH, p, p′ -DDD, p, p' -DDE concentrations were observed between the patients with PCOS and the control group. Serum p, p′ -DDT (P = 0.016) and o, p′ -DDT (P = 0.000) levels were significantly higher in patients with PCOS compared with the control group. The results of the association between OCPs levels and hormone levels indicated that o, p′ -DDT may play a role in the pathogenesis of PCOS by affecting hormones levels. Further trials should be investigated with the findings in this study to obtain new pathogenesis of PCOS. Highlights: PCOS is caused by a combination of genetic susceptibility and environmental exposures. Patients with PCOS had higher p, p′ -DDT (P = 0.016) and o, p′ -DDT levels than the controls. o, p′ -DDT may play a role in the pathogenesis of PCOS related with reproductive hormone levels.